Effect of virtual teaching and learning on the performance of veterinary students in Uruguay during the COVID-19 health emergency (FAVE Sección Ciencias Veterinarias, 2024)
The COVID-19 pandemic and the closure of educational institutions caused an immediate change from face-to-face learning to distance learning, implying adaptations of the courses to be able to offer them completely at a distance with greater use of the tools available in the Virtual Learning Environment such as the use of videoconferencing and class recording. Therefore, in this work, we conducted an analysis of the performance of students of the Faculty of Veterinary Medicine of the University of the Republic, the only institution that trains Veterinary Doctors in Uruguay, during 2020, comparing them with the performance of students during the courses of 2017, 2018 and 2019. Among the main results of this work we found that there were no significant differences in student performance, both in passing and exoneration, compared to previous years On the other hand, it was found that the career stage is strongly associated with both passing and exoneration of courses, with a low exoneration rate in the first years of the career and a high exoneration in more advanced stages.
Keywords: Veterinary Education; Virtual learning; performance